INVITRO STUDIES ON THE ANTIOXIDANT ACTIVITIES OF EXTRACTS FROM THE FLOWERS OF GOMPHRENA GLOBOSA - SHILPA SHARMA; RAVNEET K GREWAL (International Journal of Pharma and Bio Sciences, 2014)
Oxidative stress leads to formation of free radicals, reactive oxygen species and nitrogen species, which leads to numerous pathophysiological disorders. The present study is aimed to evaluate the free radical scavenging potential of flowers of Gomphrena globosa. The extracts from the flowers of Gomphrena globosa were prepared in solvents viz. methanol, ethanol and butanol. Spectrophotmetric and HPLC analysis was performed to determine total phenols, flavonoids and antioxidants with gallic acid and quercetin served as standards, respectively. The antioxidant potential of flowers of Gomphrena globosa was investigated with free radical scavenging methods, including H2O2 and DPPH as free radicals. The present findings suggested that methanol extract was more potent and had a high content of phenols and flavonoids, emphasizing the predominance of flavonoids in the extracts from Gomphrena globosa. The scavenging inhibition of H2O2 and DPPH free radicals in methanol preparations from the flowers of Gomphrena globosa were 62.3% (IC50 =13.8µg/ml) and 72% (IC50 = 10µg/ml) at 30µg/ml of extract preparations. Furthermore, positive correlation was observed between polyphenols and free radical scavenging inhibition. These observations indicate that the flowers of Gomphrena globosa may possess antioxidant properties and further pharmacological investigations could provide an insight into the potential use of these flowers in the treatment of oxidative related disorders.